1989
DOI: 10.1007/bf00144840
|View full text |Cite
|
Sign up to set email alerts
|

Aetiology of Balkan nephropathy: A reapprisal after 30 years

Abstract: Balkan nephropathy (BN) has been a complete aetiological puzzle for many years. Intense research produced many controversial results, but also helped some clues to be traced. Thus, it became rather obvious that the disease is caused by environmental factors (though it may be, to some extent, genetically controlled). Among live agents, slow viruses are the only (and theoretically very attractive) possible cause of both BN and urothelial tumours, which occur frequently in BN endemic areas. Apart from occasional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 18 publications
1
10
0
1
Order By: Relevance
“…The human pathology of BEN is a diffuse fibrosis subsequently leading to renal failure. A similar pathology was found in pigs following chronic toxicity studies conducted with OA (Radovanovic, 1989). In all species tested so far (pig, chicken, mouse, rat, dog) OA induced nephrotoxic effects, although the sensitivity of the different species varied (Kuiper-Goodman and Scott, 1989).…”
Section: Introductionsupporting
confidence: 66%
See 1 more Smart Citation
“…The human pathology of BEN is a diffuse fibrosis subsequently leading to renal failure. A similar pathology was found in pigs following chronic toxicity studies conducted with OA (Radovanovic, 1989). In all species tested so far (pig, chicken, mouse, rat, dog) OA induced nephrotoxic effects, although the sensitivity of the different species varied (Kuiper-Goodman and Scott, 1989).…”
Section: Introductionsupporting
confidence: 66%
“…Special attention has been paid to OA since a link between OA and human Balkan endemic nephropathy (BEN) was postulated (IARC, 1993;Radovanovic, 1989). However, this link has not yet been proven.…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were obtained in a crosssectional study of the village of Sopic, another seriously affected endemic village in the municipality of Lazarevac [4] . Familial clustering of cases is one of the most conspicuous features of the disease [13] .…”
Section: Discussionmentioning
confidence: 99%
“…Human Balkan nephropathy was also attributed to OTA exposure. However, although there is a considerable amount of data regarding this disease, it is still controversial whether OTA plays a causative or only a subordinate role in the induction of the human Balkan nephropathy (Berndt and Hayes, 1979;Radovanovic, 1989Radovanovic, , 1991IARC, 1993). Laboratory studies with rodents, pigs, poultry and fish have demonstrated that the kidney is the primary organ for OTA induced toxicity (Fuchs, 1988).…”
Section: Introductionmentioning
confidence: 99%